Decision Support System for The Selection of Digital Advertising Provider for Car Sales Using Weight Product Method (case Study : Pt. Media Tech Indonesia) - M. Mahaputra Hidayat; Rani Pubaningtyas; R. Dimas Adityo; Eka Ramadhana Puriyadi (JEECS (Journal of Electrical Engineering and Computer Sciences), 2022)
This research is motivated by the internet which is starting to be seen as a potential media to be used as a means ofadvertising. Compared to other media such as television, the internet offers relatively lower rates for a longerinstallation period. If it costs 20 million rupiah, an advertiser can only display one ad for one slot for two times.Conversely, for the same fee, advertisers can place weeks of advertisements on the internet. Since online advertisinghas emerged, many digital ad providers have been able to advertise a product. When individuals or their companies(customers) want to advertise products, many of them still don't understand how to use digital advertising providers.The purpose of this study is to provide an information or description in the decision to choose a digital advertisingprovider for car sellers according to customer desires.In this research, a system implemented using the Weight Product (WP) method has a vector V value that is differentfor each customer. The results of this study conducted by 20 individual customer types chose digital advertisingproviders Google Ads 30%, Facebook 55%, Instagram 10%, Youtube 5% and 20 corporate type customers chose thedigital advertising provider Google Ads 15%, Facebook 45%, Instagram. 35%, Youtube 5%. It can be concluded thatthe test results show that individual customer types tend to choose the Facebook digital advertising provider (55%),while the corporate type customers tend to choose the Facebook digital ad provider (45%).